The maturation process of incorporating sustainability in universities - Vargas, Luis; Mac-Lean Bravo, Claudia Alejandra; Huge, Jean (My University, 2019)
Purpose In the past few decades, sustainability in higher education has become ever more prevalent, although the diversity in pace of adoption and the wide range of interpretations and practices is huge. The purpose of this study is to present recent research on organizational change processes in universities. Design/methodology/approach The methodological approach applied corresponds to the social issue maturation framework, to identify, describe and assess patterns of change across higher education institutions. The maturation of sustainability in universities can be divided into four stages: emergence, popularization, formalization and maturity. Findings The findings indicate that sustainability processes often begin as ad hoc processes which grow and mature over time as a range of different actors join in. However, sustainability in universities is increasingly connected with sustainability in the private sector and with other public actors. Moreover, there is a growing acknowledgement of the interactions between society, industry and academia. Originality/value The value of the paper is to provide a critical assessment of the potential of living lab projects initiated in Belgium (Brussels) and Chile (Santiago de Chile) to anchor sustainability firmly both in the functioning of the university and in the interactions with the neighborhood. The authors reflect on the requirements and the implementation of these initiatives as a strong indication of mature sustainability integration in, and by way of, universities.
Keywords: sustainable development; universities; education; higher education; sustainability in university campuses